2014
DOI: 10.11648/j.sjph.20140205.28
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Environmental Health Services of Urban Health Extension Program and Associated Factors in Debretabor Town, North West Ethiopia: Cross Sectional Study

Abstract: Back ground: Studies in a number of countries have shown that wherever indiscriminate waste disposal is high, infant and child mortality rates are high. Although utilization of environmental health services is an important indicator for measuring success of the health extension program; data on environmental health services of urban health extension program are scarce in the study area and elsewhere in Ethiopia. Objective: To assess utilization of environmental health services of urban health extension program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
(5 reference statements)
2
5
1
Order By: Relevance
“…The result also revealed that being model in implementing HEP had a highly significant effect with utilizing of HEP. The households who were not model in HEP had higher odds of not utilizing HEP than those who were model, which is in line with the previous studies done by [16,17,19] that a model family utilized HEP more likely than non-model family.…”
Section: Discussion For Hep Utilizationsupporting
confidence: 90%
See 2 more Smart Citations
“…The result also revealed that being model in implementing HEP had a highly significant effect with utilizing of HEP. The households who were not model in HEP had higher odds of not utilizing HEP than those who were model, which is in line with the previous studies done by [16,17,19] that a model family utilized HEP more likely than non-model family.…”
Section: Discussion For Hep Utilizationsupporting
confidence: 90%
“…In this study, the household who had satisfactory knowledge, utilize more likely than those do who had unsatisfactory knowledge, similar findings were obtained by [11,17,18,19] that those who had satisfactory knowledge utilize HEP more likely than those who had not satisfactory knowledge. However, it contradicts with [16] finding done on utilization of urban health extension program at Debretabor Town.…”
Section: Discussion For Hep Utilizationcontrasting
confidence: 82%
See 1 more Smart Citation
“…Previous literature found that the health extension program primary health care service coverage is not similar with each previous study those differences in urban and rural areas includes: community uptake of family planning service, improvement of maternal and child immunization service, <5 child diarrhea disease prevention and treatment, graduation of model household or open defecation free kebelle, and solid and liquid waste management practice in the country [9][10][11][12]. Nevertheless, shortage of published literature in the study setting to investigate attitude and participation level of household members towards health extension program service accomplishment in urban areas to improve primary health care service utilization [11,12]. There were also one hospital, three public health centers and more than 10 private higher and medium clinics were provision of health care services for the communities reside in the urban.…”
Section: Introductionmentioning
confidence: 91%
“…Health extension service utilization. Anyone who implements at least 75% of the national health extension program packages [16].…”
Section: Operational Definitionsmentioning
confidence: 99%